2014
DOI: 10.4269/ajtmh.13-0279
|View full text |Cite
|
Sign up to set email alerts
|

Private Sector Provision of Oral Rehydration Therapy for Child Diarrhea in Sub-Saharan Africa

Abstract: Abstract. Although diarrheal mortality is cheaply preventable with oral rehydration therapy (ORT), over 700,000 children die of diarrhea annually and many health providers fail to treat diarrheal cases with ORT. Provision of ORT may differ between for-profit and public providers. This study used Demographic and Health Survey data from 19,059 children across 29 countries in sub-Saharan Africa from 2003 to 2011 to measure differences in child diarrhea treatment between private for-profit and public health provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…We also found that mean daily temperature was associated with incident diarrhea though not with cholera. Previous analyses of non-cholera diarrhea from Bangladesh have shown a similar trend of increasing diarrhea with increasing temperature [ 30 , 31 ], though a more nuanced relationship with cholera and temperature has been noted in other analyses [ 32 ]. Our estimates of the relationship between lagged ORS sales and diarrhea and cholera suggest that future predictive models should consider the influence of temperature on the relationship between sales and incidence.…”
Section: Discussionmentioning
confidence: 87%
“…We also found that mean daily temperature was associated with incident diarrhea though not with cholera. Previous analyses of non-cholera diarrhea from Bangladesh have shown a similar trend of increasing diarrhea with increasing temperature [ 30 , 31 ], though a more nuanced relationship with cholera and temperature has been noted in other analyses [ 32 ]. Our estimates of the relationship between lagged ORS sales and diarrhea and cholera suggest that future predictive models should consider the influence of temperature on the relationship between sales and incidence.…”
Section: Discussionmentioning
confidence: 87%
“…We could not test socio-economic or geographic differentials in 2-week prevalence of diarrhea and case management indicators since the data analysed were aggregated. However, association of diarrhea with lower socio-economic status has been illustrated in previous reports [35, 38] and geographic variations within countries are well documented in DHS reports [32]. The validity of the indicators that were carefully selected by the WHO and UNICEF after field studies and technical consultations, has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies performed in South India and Sub-Saharan Africa have shown that, regardless of receiving formal diarrhea management training, healthcare professionals treating children with diarrhea tended to prescribe more antibiotics, injections and anti-diarrheal medications than oral rehydration solutions and zinc Sood & Wagner, 2014). Efforts are therefore needed to evaluate healthcare professionals' clinical management of childhood diarrhea in the most affected area of the globe.…”
Section: -Introductionmentioning
confidence: 95%